Population-based evaluation of the Ehrlichia ruminantium MAP 1B indirect ELISA - Peter, T.F.; O'Callaghan, C.J.; Medley, G.F.; Perry, Brian D.; Semu, S.M.; Mahan, S.M. (Springer, 2001)
The indirect MAP 1B ELISA based on the recombinant MAP 1B fragment of the immunodominant MAP 1 protein of Ehrlichia ruminantium is considered to be the most sensitive and specific assay for the serodiagnosis of heartwater. In this study, we evaluated its reliability in detecting exposure to E. ruminantium in field populations of domestic ruminants in Zimbabwe. Cattle and goat herds in endemically stable areas with high infection pressure and an expected close to 100% prevalence of E. ruminantium exposure were sampled. Bovine sera (n=858) and caprine sera (n=706) collected at 7 locations representative of the 2 main production systems (communal lands and large scale commercial farms) in the 2 main agroecological zones of Zimbabwe (highveld and lowveld) were analysed. The prevalence of MAP 1B-specific antibodies in goats was similar and high, ranging from 67 to 100%, at all except one site (43%). Age-specific differences in goats (1, 2, 3, 4, and 5 years) were not observed. In contrast, MAP 1B seroprevalence in cattle was significantly lower (P < 0.001), ranging from 46 to 61% in the lowveld communal area and from 24 to 33% in the remaining areas (P < 0.001). Age-specific differences in seroprevalence (1, 2, 3, 4, and 5-7+years) were similarly not evident in cattle (P < 0.15). Hence, the indirect MAP 1B ELISA may be an unreliable indicator of past exposure to heartwater in field-infected cattle in Zimbabwe. Although the reasons for this low response in field cattle are not fully understood, this study illustrates the need for field validation of the performance of new diagnostic tests prior to their use for epidemiological purposes.